2009
DOI: 10.1623/hysj.54.1.101
|View full text |Cite
|
Sign up to set email alerts
|

A review of the potential impacts of climate change on surface water quality

Abstract: It is now accepted that some human-induced climate change is unavoidable. Potential impacts on water supply have received much attention, but relatively little is known about the concomitant changes in water quality. Projected changes in air temperature and rainfall could affect river flows and, hence, the mobility and dilution of contaminants. Increased water temperatures will affect chemical reaction kinetics and, combined with deteriorations in quality, freshwater ecological status. With increased flows the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
561
0
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,026 publications
(630 citation statements)
references
References 133 publications
16
561
0
12
Order By: Relevance
“…However, as stated for example by Skeffington et al (2007), translating input uncertainties into uncertainty in the outputs is typically less than the summed uncertainty in the input parameters. Whitehead et al (2009) suggests that complex behaviour patterns can surprisingly reduce variability in model outputs. Therefore, it can be reasonably stated that the final uncertainty of the modelling chain is of the same order of magnitude than the uncertainty of the single models.…”
Section: Impacts On Phytoplankton Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as stated for example by Skeffington et al (2007), translating input uncertainties into uncertainty in the outputs is typically less than the summed uncertainty in the input parameters. Whitehead et al (2009) suggests that complex behaviour patterns can surprisingly reduce variability in model outputs. Therefore, it can be reasonably stated that the final uncertainty of the modelling chain is of the same order of magnitude than the uncertainty of the single models.…”
Section: Impacts On Phytoplankton Concentrationmentioning
confidence: 99%
“…However, the effect of environmental change on phytoplankton blooms and its consequences on water quality has only been addressed recently for lakes (Elliott, 2012;Thackeray et al, 2008), and not yet tackled for river systems, except through some qualitative description of potential impacts by Arnell et al (2015), Johnson et al (2009) and Whitehead et al (2009). These studies agree that phytoplankton are likely to increase their concentration above current levels in the future (Johnson et al, 2009), due to lower flows, reduced velocities and higher water residence (Whitehead et al, 2009), also reducing oxygen levels in rivers (Whitehead et al, 2009). An important step forward would be to develop a quantitative approach to assess the effects of environmental change on phytoplankton populations in river systems.…”
Section: Introductionmentioning
confidence: 99%
“…The pressures are further exacerbated by the effect of a changing climate, which is predicted to bring more frequent extreme events (Kendon et al, 2014;Murphy et al, 2009), resulting in the likelihood of more winter runoff and longer periods of low flow Wilby et al, 2006), although still with much uncertainty (Arnell, 2011;Kay and Jones, 2012;Prudhomme et al, 2012). In conjunction with projected climatic changes, previous studies have indicated likely increases in sediment and nutrient loads (Crossman et al, 2014;El-Khoury et al, 2015;Jeppesen et al, 2009;Jeppesen et al, 2011;Macleod et al, 2012;Rankinen et al, 2015;Whitehead et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, global warming is expected to promote an increasing number of cyanoHABs episodes (Paerl, 2009;Whitehead et al, 2009;Wilk-Woźniak et al, 2016).…”
Section: Discussionmentioning
confidence: 99%